Review of World Bank Engagement in the Irrigation and Drainage Sector in Azerbaijan - World Bank (Washington, DC, 2013)
The sector review includes seven chapters and one annex. This first chapter is an overview of agriculture, irrigation and the purpose and content of this report. The second chapter provides a review of the Bank s own strategy and priorities for irrigation and drainage within its portfolio of investments, from the time of its 2004 Strategy until the present. It also includes a short summary of key lessons learned in this sector. The third chapter provides a brief situation analysis for irrigation and drainage in Azerbaijan, including a description of key parameters and changes; a description of rising challenges, needs and opportunities; and an overview of the Government s State Program (SP) for Sustainable Development of Amelioration and water management for 2008-2015. The fourth chapter describes the issues of investment and financing of irrigation and drainage priorities for infrastructure development, rehabilitation and modernization, and management. This includes investment priorities for the Government as well as needs for cost recovery by water users for the cost of irrigation and drainage system operations and maintenance. The fifth chapter describes the institutional framework and how it has emerged since independence. It also identifies outstanding issues for further institutional development, both for the Government and for water users associations (WUA). The sixth chapter describes the implications of climate change for the vulnerable irrigation and drainage sector in Azerbaijan. Suggestions are provided for a process to prepare an adaptation strategy for climate change. The seventh chapter identifies ten key priorities for investments in the irrigation and drainage sector in Azerbaijan. These priorities are based on the views of staff of the World Bank, staff of the AIOJSC (Amelioration and Irrigation Open Joint Stock Company), selected consultants and the author.